Software base logic analyzer and Signal Generator Application / Lee Kean Kian - Lee , Kean Kian (2004)
The logic analyzer and signal generator application is a system where user can input and output through the parallel port. For the logic analyzer application, certain pins of parallel port are "on" by user. There will be a output display on computer. For signal generator application, the parallel port pins will be activated by pressing buttons on a user interface. The parallel port will be connected to a logic analyzer hardware. The output will be display on interface of logic analyzer. There will be additional function of the application. Software based logic analyzer and signal generator have security feature where every user that uses to the software have to login before using the software. If the user login the wrong user identificati n and password, then an error message will be displayed. User have to re-login again until the correct user identification and password is typed.The main advantage of the application is that it can be used to test , FPGA or other electronic circuits.